Neurologic manifestations of intravascular large B-cell lymphoma. Issue 1 (February 2016) - Tahsili-Fahadan, Pouya; Rashidi, Armin; Cimino, Patrick J.; Bucelli, Robert C.; Keyrouz, Salah G.
Abstract: Purpose of review: Intravascular large B-cell lymphoma is a rare subtype of large B-cell lymphoma that affects various organs including the nervous system. The diagnosis is challenging and frequently made at autopsy. Recent findings: We report 5 cases with an array of neurologic manifestations. All patients were initially evaluated for alternative diagnoses. Three patients were diagnosed at autopsy, one with brain biopsy, and another with muscle biopsy. Muscle was involved in all 3 patients who had muscle tissue available for analysis. Summary: Our observations suggest that random open muscle biopsy may present a high-yield, less invasive option for the diagnosis of this disorder.